Usagi yojimbo (1987), volume 33 ebook The hidden. - Sakai, Stan (Usagi Yojimbo (1987),, 2019)
Usagi and his friend Inspector Ishida join forces once again as they embark on a mission to track down and uncover the importance of a foreign book that's been at the root of many problems across the land. The daring duo, desperate to solve the mystery and restore peace, are forced to undertake unusual measures as well as enlist the help of a few surprising sources to get the information they require. Will Usagi and Ishida come out victorious or will this mystery prove too much for them to solve? Collecting a complete story arc in one place, this is the perfect jumping-on point for any fans--new or old! Collects Usagi Yojimbo: The Hidden issues #1-#7.